MAKNA HADIS TENTANG KHITAN PEREMPUAN DAN MITOS-MITOS YANG MENYERTAINYA - Husnul Khotimah; Anisatun Muthi’ah; Lukman Zain Muhamad Sakur (IAIN Syekh Nurjati Cirebon, 2021)
The custom of the Muslim community to perform female circumcision is based on the traditions of the Prophet and is supported by certain myths. Meanwhile, Islamic jurists do not agree with one opinion regarding circumcision. Imam Malik thinks that female circumcision is a sunnah. Imam Shafi’i and Ahmad declared it obligatory. Imam Abū Hanifah only said that circumcision is a good practice. This raises the question of whether the traditions about female circumcision are authentic or not and whether the accompanying myths can be trusted. This study reveals the quality of the circumcision hadith and the myths that accompany it with a qualitative approach, literature review. Research shows that the hadiths about female circumcision are da’īf al-sanad. Therefore the myths about circumcision cannot be trusted.